KEBERTAHANAN NILAI RELIGI DAN KEBERLANJUTAN KEPEMIMPINAN PEREMPUAN DALAM PERGELARAN MAENGKET MAKAMBERU - Rattu, Jultje Aneke (Masyarakat Indonesia, 2018)
This research discusses religious value’s survival and women’s leadership sustainability of Minahasan in Maengket Makamberu oral tradition. Religious ceremony performances that became on of the performing arts in globalization era has reappeared and integrated with the performing arts in glocalization one. This research uses a qualitative approach and ethnography method with multidisciplinary concepts, such as oral tradition of Vansina, Ong, and Finnegan, mentalité of Braudel, and gender of Oakley. The results has found that the performances cannot be generalized because their forms are influenced by cultural, social, situational, and ideological contexts. The religious performances have resurfaced in glocalization because the Minahasan’s mentalité has survived. It leads to women’s leadership in performances has continued, although the ideological context has been influenced by patriarchal system of Christian or Catholic religion. Therefore, it can be concluded that Minahasan performance forms are influenced by the survival of their contexts and religious values and the continuation of women’s leadership caused by their mentalité.